THE PRIORITY NEEDS FOR DEVELOPING ACADEMIC MANAGEMENT OF BODINDECHA (SING SINGHASENI) AFFILIATED SCHOOLS BASED ON THE CONCEPT OF EMOTIONAL INTELLIGENCE - Yansalee, Bunyarit; Petpon, Ponglikit (Journal of Educational Review Faculty of Education in MCU, 2024)
The purpose of this research is to study the priority needs for developing academic management of Bodindecha (sing singhaseni) affiliated schools, according to the concept of Emotional intelligence. A descriptive research method is used in this research. The tools used in the research were questionnaires. The data were analyzed by arithmetic mean, standard deviation, and the modified Priority Needs Index (PNIModified). The survey was completed by 251 people, who were all administrators and secondary school teachers at Bodindecha (sing singhaseni) affiliated schools. The finding showed that 1) Current conditions were at a moderate level, with the teaching and learning having the highest mean and the measurement and evaluation having the lowest mean. The desired condition was at a high level, with the measurement and evaluation having the highest mean and teaching and learning with the lowest mean. 2) With the Priority Need Index, the academic concept was 0.358 overall (PNIModified = 0.358). In consideration of the scope of academic management, it was measurement and evaluation with the highest order of needs, followed by the teaching and learning management with the lowest order of needs.